Method to determine specialization of Ukraine at the international market - E. I. Voynova (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The problem of statistical data processing, which is commonplace in analysis of statistical indicators, is even more important in assessing global tendencies, given more than two hundred states and state groups with a lot of indicators, and for analysis to be reliable all the indicators need to be covered. The aim of the study is to construct a simple method for processing the statistical data, to allow for assessment of economic trends at country level in the global context. The method is constructed on the basis of data on the Ukrainian exports and imports of goods and the geography of Ukraine’s global trade.The proposed method has the following algorithm. First, specialization of Ukraine is determined through calculating the share of each country (201 countries), and Ukraine in particular, in global exports and imports of goods in 2014. Second, criteria for grouping the countries by share in world exports / imports are fixed: more than 5% (Exl /Iml), from 1 to 5% (Ex2 / Im2),from 0.1 to 1% (ЕхЗ /1 m3), 0.01 to 0.1% (Ex4/Im4), 0.001 to 0.01% (Ex5 / Im5), from 0.0001 to 0.001%> (Ex6/lm6), less than 0.0001% (Ex7/lm7). Third, 7x7 matrix (by number of criteria) is filled with measures derived for the countries. The same principle is applied to derive the measures for each trade partner of Ukraine and the whole range of goods traded globally by Ukraine.The proposed method and testing its performance by data on the Ukrainian exports-imports has shown its capacity for analysis of a large set of economic indicators, which allows for providing qualitative characteristics of the full sample of indicators and ensuring the reliability of the analysis.